Interference of nail polish on the peripheral oxygen saturation in patients with lung problems during exercise La interferencia del esmalte de uñas en la saturación periférica de oxígeno en pacientes con pneumopatía en el ejercicio Interferência do esmalte de unha na saturação periférica de oxigênio em pacientes pneumopatas no exercício - Walkiria Shimoya-Bittencourt; Carlos Alberto de Castro Pereira; Solange Diccini; Ana Rita de Cássia Bettencourt (Universidade de São Paulo, 2012)
AIM: To assess the interference of nail polish on the reading of peripheral oxygen saturation in patients with chronic obstructive pulmonary disease on the step exercise. METHODS: In this study, there was the inclusion of patients with chronic obstructive pulmonary disease, current non-smokers, of both sexes. Four different colours of nail polish were used in the present study (base, light pink, red and brown), randomly distributed among the fingers of the right hand, with the corresponding fingers on the opposite hand being controls. Saturation was measured at rest, with and without the polish, and also during the 4th, 5th and 6th minutes of the exercise programme. RESULTS: The experimental universe included 42 patients with ages of 62.9±8.7 years. In the exercise considered, the red colour reduced it in the fourth minute of the exercise (p=0.047). In contrast, the brown colour reduced saturation at rest and also during the course of exercise (p=0.01). CONCLUSION: In patients with chronic obstructive pulmonary disease, the red and brown colours interfered with the reading of the peripheral oxygen saturation during exercise. This study is registered at the Brazilian Register of Clinical Trials (Registro Brasileiro de Ensaios Clínicos) under No. RBR-9vc722. OBJETIVO: Evaluar la interferencia del esmalte de uñas en la lectura de la saturación periférica de oxígeno en pacientes con enfermedad pulmonar obstructiva crónica en el ejercicio de la etapa. MÉTODOS: Fueron incluidos pacientes con enfermedad pulmonar obstructiva crónica estable, no fumadores actuales, de ambos los sexos. Fueron utilizadas cuatro colores de esmalte (base, rosa claro, rojo y marrón) distribuidas aleatoriamente entre los dedos de la mano derecha teniendo los dedos contralaterales como control. La saturación fue medida en reposo con y sin esmalte y durante el 4º, 5º y 6º minutos del ejercicio. RESULTADOS: Fueron incluidos 42 pacientes con edad de 62,9±8,7 años. En el ejercicio el color rojo apocó la misma en el cuarto minuto de ejercicio (p=0,047). El color marrón redujo la saturación en el reposo y durante el ejercicio (p=0,01). CONCLUSIÓN: En pacientes con enfermedad pulmonar obstructiva crónica los colores marrón y rojo interfieren en la lectura de la saturación periférica de oxígeno en el ejercicio. Este estudio está registrado en el Registro Brasileño de Ensayos Clínicos bajo el número de registro: RBR-9vc722. OBJETIVO: avaliar a interferência do esmalte de unha na leitura da saturação periférica de oxigênio em pacientes com doença pulmonar obstrutiva crônica, no exercício do degrau. MÉTODOS: foram incluídos pacientes com doença pulmonar obstrutiva crônica estável, não fumantes atuais, de ambos os sexos. Utilizaram-se quatro cores de esmalte (base, rosa claro, vermelho e marrom), distribuídas aleatoriamente entre os dedos da mão direita, tendo os dedos contralaterais como controle. A saturação foi medida em repouso com e sem esmalte e durante o 4º, 5º e 6º minutos do exercício. RESULTADOS: foram incluídos 42 pacientes com idade de 62,9±8,7 anos. No exercício, a cor vermelha diminuiu a mesma no quarto minuto de exercício (p=0,047). A cor marrom reduziu a saturação no repouso e durante o exercício (p=0,01). CONCLUSÃO: em pacientes com doença pulmonar obstrutiva crônica, as cores marrom e vermelha interferem na leitura da saturação periférica de oxigênio no exercício. Este estudo está registrado no Registro Brasileiro de Ensaios Clínicos, sob número de registro: RBR-9vc722.